PENGARUH CONTENT MARKETING DAN EVENT MARKETING TERHADAP CUSTOMER ENGAGEMENT DENGAN SOSIAL MEDIA MARKETING SEBAGAI VARIABEL MODERASI DI PAKUWON CITY - Johan Ardi Limandono (Jurnal Strategi Pemasaran, 2017)
The development of the digital age today has affected the world of marketing. Where every company competes to show who is the best. Where now in the form of a good promotion is no longer using advertising in general, but more use on content marketing.               This study aims to analyze the influence of marketing content and event marketing to customer engagement with social media marketing as moderation variable in Pakuwon City.               The study was conducted by distributing questionnaires to 100 respondents of East Coast Center and Food Festival visitors, Pakuwon City. The analysis technique used is quantitative analysis technique with path analysis method.               The result of this research said that content marketing have a siginificance effect to customer engagement. And also event marketing had a significance effect to customer engagement. But sosial media marketing still not yet had an effect as moderation variable from content marketing to customer engagement. Yet social media marketing was succes become a moderation variable for event marketing to customer engagement.